Oncology Section EDGE Task Force on Cancer: A Systematic Review of Clinical Measures for Pain. Issue 2 (April 2018) - Harrington, Shana E.; Gilchrist, Laura; Lee, Jeannette; Westlake, Frances L.; Baker, Alicia
Abstract : Background: Pain is one of the most common complaints in individuals with cancer and can occur at any point during the course of cancer treatment. Purpose: To identify outcome measures for assessing pain and to evaluate their psychometric properties and relevance to adults with a diagnosis of cancer. Methods: Three electronic databases (CINAHL, MEDLINE, and PsycINFO) were reviewed using specific search terms to locate articles that identify outcome measures assessing pain in adults with a diagnosis of cancer. From the 1164 articles identified, 494 articles were reviewed and 22 outcome measures were selected for analysis. Each outcome measure was independently reviewed and rated by 2 reviewers using the updated Cancer EDGE Task Force Outcome Measure Rating Form. Any discrepancies between reviewers were discussed, and an overall recommendation for each measure was made using the 4-point Cancer EDGE Task Force Rating Scale. Results: On the basis of the psychometric properties, clinical utility, and relevance to adults with a diagnosis of cancer, the following 3 measures are highly recommended: McGill Pain Questionnaire–Short Form, Numeric Rating Scale, and Visual Analog Scale. Four measures are recommended: Brief Pain Inventory, Brief Pain Inventory–Short Form, McGill Pain Questionnaire, and Pain Disability Index. Eleven measures are recommended as reasonable to use, and 3 are not recommended. Conclusions: Seven of the 22 pain measures demonstrated satisfactory psychometric properties and clinical utility and are thereby recommended for clinical and research use in adults with a diagnosis of cancer.